Role of physical factors in the pathogenesis of bullous pemphigoid: Case report series and a comprehensive review of the published work. Issue 2 (15th July 2015) - Dănescu, Sorina; Chiorean, Roxana; Macovei, Victorina; Sitaru, Cassian; Baican, Adrian
Abstract: Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease affecting mainly the elderly. The subtype of the disease induced by physical agents represents a rare and, therefore, insufficiently characterized form. In the present study, we aimed to contribute to a better understanding of the pathogenetic mechanisms involved in the onset of BP induced by different trigger factors. We have retrospectively analyzed nine cases of BP. All patients were characterized based on clinical, epidemiological and immunological parameters. For each case, the trigger factor involved was specified. In addition to our retrospective analysis, a comprehensive review of the 59 published cases was conducted, regarding the involvement of trigger factor in BP, and clinical, epidemiological and immunological data were collected. In the local study, conducted on nine patients diagnosed with BP, various trigger factors were identified: contrast substance injection, surgical procedure, mechanical trauma, insect bite, thermal burn, radiotherapy and ultraviolet exposure associated with pre‐existing psoriasis. The autoantibodies from all patients were shown to activate granulocytes and induce dermal–epidermal split. Different hypotheses regarding the pathogenetic mechanism involving the trigger factors have been discussed. In regard of the pathogenetic mechanism, we believe that the most reliable hypothesis is that BP patients already have low titers of anti‐basement membrane autoantibodies which activate the granulocytes. However, more studies are needed for a better understanding of the pathogenetic mechanism of the intervention of trigger factors.